Epidemiology of Preterm Delivery in Benin City. - Ibhanesebhor SE; Afadapa MA (Nigerian Journal of Paediatrics, 2024)
Summary:. In a retrospective study, the epidemiology of preterm deliveries over a six-year period in Benin City, was assessed. The overall incidence of preterm deliveries was 6.2 percent and this showed an increasing trend over the years. The mean birthweight was 1683gms, mean gestational age 32 weeks and mean maternal age 28 years. A high mortality rate of 34.9 percent was recorded among the preterin deliveries during the neonatal period. Gestational age <28 weeks and birthweight <1000 grams were each asso ciated with a mortality rate of over 95 percent. More preterin deliveries took place during the rainy season, a period of higher malaria infection and physical stress. Caesarean section delivery offered no distinct advantage over vaginal delivery for preterm mortality. Primiparity and grandmultiparity were associated with higher mortality rates, whereas maternal age had no effect on preterm mortality rate.